Comparison of water-soluble and exchangeable forms of Al in acid forest soils - Drabek, Ondrej; Mladkova, Lenka; Boruvka, Lubos; Szakova, Jirina; Nikodem, Antonin; Nemecek, Karel (Journal of inorganic biochemistry, 2005)
Soil acidification promotes Al release from minerals and parent bedrocks; it also affects Al mobilization and speciation. Speciation of KCl extractable and water-extractable Al in forest soils was done by means of HPLC/IC method. Species Al3+ were the most abundant Al forms in the KCl extracts (around 93%). Prevailing Al forms (more than 70%) in aqueous extracts were Al(X)1+, [i.e., Al(OH)2+, Al(SO4)+, AlF2+, Al(oxalate)+, Al(H-citrate)+, etc.] species. It is assumed that most of KCl and water-extractable Al is bound in soil sorption complex (i.e., highly dispersed colloidal fraction of the soil solid phase creating negative charge) where majority of Al exists in the form of Al3+ species. The ECEC values, total carbon content and parameters related to soil organic matter composition (N and S content) have apparent effect on Al speciation. The most toxic Al3+ species are more concentrated in the B horizons compared to the A and E horizons. Aqueous extracts simulate Al release to soil solution under normal conditions; it can thus exhibit the actual Al toxicity. On the other hand, KCl extraction describes a potential threat for case of strong disturbance of natural soil conditions.